Global, regional, and national burden of very early-onset colorectal cancer and its risk factors from 1990 to 2019: A systematic analysis for the global burden of disease study 2019 - Zhen Junhai; Meng Yang; Tan Zongbiao; Yan Wenxuan; Li Tiange; Wu Yanrui; Liu Chuan; Dong Weiguo (Neoplasia: An International Journal for Oncology Research)
Aims: Very early-onset colorectal cancer (EOCRC) was defined as CRC diagnosed before the age of 35 proposed by the latest EOCRC management guideline. Until now, the disease burden of very EOCRC has never been reported. This study aimed to explore the burden of very EOCRC across the past three decades. Methods: We extracted the data from Global Burden of Disease Study to analyze the disease burden of very EOCRC. Risk factors for the burden of deaths and disability-adjusted life years (DALYs) due to very EOCRC were also explored in this study. Additionally, decomposition analysis and frontier analysis were also conducted. Results: Despite regional and gender variations, the global very EOCRC incidence cases increased from 21,874 (95 % UI: 20,386-23,470) to 41,545 (95 % UI: 37,978-45,523). Besides, the deaths cases also increased from 11,445 (95 % UI: 10,545-12,374) to 15,486 (95 % UI: 14,289-16,803), and the DALYs cases increased from 718,136 (95 % UI: 659,858-778,283) to 961,460 (95 % UI: 886,807-1,042,734). Decomposition analysis revealed the epidemiological change contributed most to the incidence burden of very EOCRC. Countries or regions with Sociodemographic Index (SDI) between 0.4 and 0.8 had greater disease burden improvement potential through frontier analysis. Diet low in milk, diet low in calcium, alcohol use, and high body-mass index were the main contributors to deaths and DALYs. Conclusions: The increase in CRC burden among populations younger than 35 years globally requires vigilance from policy makers, physicians, and young individuals themselves, especially those regions experiencing faster growth burden of very EOCRC.